BUKU BESAR, CUAN BESAR: STRATEGI AKUNTANSI UNTUK BISNIS ANTI BANGKRUT - Lina Herlina; Maria Evy Purwitasari; Aris Nur Hasan; Dwi Okty Utami; Suparti Suparti (JURNAL LENTERA AKUNTANSI, 2025)
This study aims to analyze the role of accounting strategy implementation, particularly the principle of accounting conservatism, in enhancing business resilience and preventing bankruptcy risk among Micro, Small, and Medium Enterprises (MSMEs). The research employed a descriptive quantitative approach using a survey technique involving 35 MSME actors in the Greater Jakarta (Jabodetabek) area. Data were collected through structured questionnaires addressing financial recording practices, preparation of financial statements, cash flow management, and the application of prudence principles in revenue and expense recognition. Data analysis was conducted using descriptive statistics and simple correlation analysis. The results indicate that MSMEs that regularly maintain general ledger records, prepare income statements and balance sheets, and apply conservatism principles (not rushing to recognize profits and recognizing potential losses more promptly) demonstrate higher levels of cash flow stability and business resilience. These findings confirm that prudence-based accounting strategies play a significant role in maintaining liquidity and reducing the potential for bankruptcy. The implication of this study highlights the importance of practical accounting literacy for MSME actors as a fundamental foundation toward sustainable and financially resilient businesses.